Role of multidetector CT Urography in patients with hematuria - Parajuli, Santwana; Narayan Regmi, Yukta; Sharma, Bhojraj; Paudel, Nawaraj; Sharma, Pujan; Sharma, Keshab (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: With the advancement in imaging abilities like thin slicing, volume rendering and 3D reconstruction, multidetector CT urography has been a preferred over other imaging modalities for the comprehensive assessment of kidney, ureter and bladder. Hematuria is one of the commonly encountered complaints of patients in hospital. The aim of our study was to evaluate the role of Multidetector computer tomographic urography in hematuria and guiding the clinician to find cause and manage it.Methods: A hospital based prospective cross-sectional study conducted among 228 patients in the duration of one year who presented with either gross or microscopic hematuria and fulfilled the inclusion criteria. Data collected were analyzed using Statistical Package for Social Sciences version 26.0.Results: Patients commonly presented with gross hematuria 148(64.9%). Most common cause of hematuria as per our study was urolithiasis, 103 patients. Calculus predominantly involved kidney 66(64%) or kidney and ureter 14(13.5%). Hydronephrosis was seen in 87(38.2%) of patients and hydroureter in 37(15.4%) of patients. Normal excretion was observed in 202(88.6%) patients whereas delayed excretion and non-excretion was seen in 13(5.7%). Infection/inflammatory conditions occurred in 34(14.9%) patients, pyelonephritis 17(50%) and cystitis 11(32.3%) being the common occurrences. Most common benign mass occurred in kidney, 65% of all renal masses. Bladder mass was found to be malignant in 80% of the detected bladder masses. Out of five detected adnexal masses, 3(60%) was found to have benign characteristics. Incidental findings included spectrum of diseases and disorders that included anatomical variants, lesions in other sites and congenital defects.Conclusions: With the findings from our study, we can conclude that MDCT Urography is found to be highly accurate in detecting the causes of hematuria and guide in timely management. It is also useful in detection of other underlying conditions with the incidental findings.